2019
DOI: 10.1124/jpet.119.257071
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pharmacokinetics Imaging by Noninvasive Heart Fluorescence Tomography and Application to Kidney Glomerular Filtration Rate Assessment

Abstract: In mouse pharmacokinetic (PK) studies, current standard methods often require large numbers of animals to support collection of blood samples serially over a defined time range. We have developed and validated a noninvasive fluorescence molecular tomography (FMT) heart imaging approach for blood PK quantification that uses small numbers of mice and has the advantage of repeated, longitudinal live imaging. This method was validated using a variety of near infrared (NIR) fluorescent-labeled molecules, ranging in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The modeling approach for deconvolution of plasma PK from dynamic heart imaging data is very useful because: a) plasma PK analysis and imaging studies can be conducted in a single cohort of animals, substantially reducing the number of animals and conserving resources; b) it improves the accuracy and precision of Patlak plot parameter estimates since the plasma PK and dynamic imaging data are obtained from the same mouse. Although bulk heart imaging data has been found to agree with plasma PK of probes that are restricted to the vascular space (Bao, Vasquez et al 2019), it is not applicable to molecules that are substantially taken up by the heart tissue. For example, a previous study reported that heart ROI time-activity curves (TACs) can overestimate the actual blood concentration of 18 F-FDG especially at later time points after injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modeling approach for deconvolution of plasma PK from dynamic heart imaging data is very useful because: a) plasma PK analysis and imaging studies can be conducted in a single cohort of animals, substantially reducing the number of animals and conserving resources; b) it improves the accuracy and precision of Patlak plot parameter estimates since the plasma PK and dynamic imaging data are obtained from the same mouse. Although bulk heart imaging data has been found to agree with plasma PK of probes that are restricted to the vascular space (Bao, Vasquez et al 2019), it is not applicable to molecules that are substantially taken up by the heart tissue. For example, a previous study reported that heart ROI time-activity curves (TACs) can overestimate the actual blood concentration of 18 F-FDG especially at later time points after injection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted by Bao et.al compared noninvasive heart fluorescence molecular tomography (FMT) and serial blood sampling to determine blood PK of probes ranging from 2-150 kDa. They found excellent agreement in kinetic profiles and associated PK parameters between these two methods and further applied FMT to estimate glomerular filtration rate under various pathological conditions (Bao, Vasquez et al 2019).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To construct the plots for [ 125 I]­iodo-Aβ42 and [ 125 I]­iodo-Aβ40, the concentrations measured in the heart ROI during the imaging experiment were used as a surrogate for the plasma concentrations. The use of heart imaging data as a surrogate for plasma pharmacokinetics is a well-established method, but was not suitable for the [ 125 I]­iodoinsulin studies due to substantial accumulation of insulin in the heart tissue. Although the concentrations derived from heart ROI do not reflect the true plasma concentrations, this approach still allows for a relative comparison of K i estimates between groups.…”
Section: Methodsmentioning
confidence: 99%
“…However, the sample size was small ( n = 3), and the PK curve of the fluorescent signal of the kidneys was inconsistent with that of the plasma concentration. The author did not explain possible reasons for this difference [ 72 ]. Additionally, this method requires continuous anesthesia, which may influence the GFR.…”
Section: Other Methodsmentioning
confidence: 99%